Managing Religious Practices and Purchases: An Exploratory Research on Christian Consumers in Burkina Faso - Nasse, Theophile Bindeoue; Sall, Fatou Diop; Ouedraogo, Alidou; Fall, Ndeye Astou Manel; Kpinpuo, Stephen; Naatu, Felicia (International Journal of Social Sciences Perspectives, 2022)
Many researchers have shown that religious factors are some motives for consumption. While a lot has been covered on the topic, some aspects are still to be discovered. A little is known on religious practices and purhase in Africa and particularly in the context of Burkina Faso. The purpose of this paper is to bring out the link between religious practices and the motives for beverages purchase by consumers. Burkina Faso is characterised by an extraordinary religious practice and an important purchase of beverages. It is important to know the reasons that lead some believers to purchase non-alcoholic industrial drinks, rather than alcohol industrial drinks. This complexity of consumer behavior and the lack of human knowledge of marketing, and of the explanatory factors of consumer behavior constitute barriers that become some management challenges for the marketing of bevrages. The methodology adopted in this research includes a qualitative approach. Qualitative data is collected from consumers. The number of semi-structured interviews considered in this research is 12. The collected data is transcribed by hand, and then it is analysed. First, the results show that high religious practices favors purchases of non-alcoholic beverages in the context. Second, the results show that low religious practices reduces purchases of non-alcoholic beverages in the same context.